2020
DOI: 10.1111/epi.16762
|View full text |Cite
|
Sign up to set email alerts
|

Contemporaneous evaluation of patient experience, surgical strategy, and seizure outcomes in patients undergoing stereoelectroencephalography or subdural electrode monitoring

Abstract: ObjectiveIntracranial electrographic localization of the seizure onset zone (SOZ) can guide surgical approaches for medically refractory epilepsy patients, especially when the presurgical workup is discordant or functional cortical mapping is required. Minimally invasive stereotactic placement of depth electrodes, stereoelectroencephalography (SEEG), has garnered increasing use, but limited data exist to evaluate its postoperative outcomes in the context of the contemporaneous availability of both SEEG and sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 44 publications
(62 reference statements)
1
18
0
Order By: Relevance
“…In this context, the surgical risks of invasive EEG, regardless of the modality (SDE or SEEG), are often justifiable to improve patient survival and quality of life 7,34 . However, current data comparing the 2 modalities are limited to expert‐opinion review articles, 3,35–37 single‐center descriptive studies with insufficient sample size to compare outcomes, 7,38 an exclusive focus on surgical complications and length of stay favoring SEEG, 4 with the 2 single‐center case series on the topic reporting unadjusted estimates of seizure freedom (1 with equivalent outcomes between SEEG and SDE, 5 and 1 with better outcomes of SEEG compared with SDE 2 ). All studies reported important differences in the baseline characteristics of patients who had SDE versus SEEG, limiting any meaningful conclusions on how the 2 modalities truly compare.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, the surgical risks of invasive EEG, regardless of the modality (SDE or SEEG), are often justifiable to improve patient survival and quality of life 7,34 . However, current data comparing the 2 modalities are limited to expert‐opinion review articles, 3,35–37 single‐center descriptive studies with insufficient sample size to compare outcomes, 7,38 an exclusive focus on surgical complications and length of stay favoring SEEG, 4 with the 2 single‐center case series on the topic reporting unadjusted estimates of seizure freedom (1 with equivalent outcomes between SEEG and SDE, 5 and 1 with better outcomes of SEEG compared with SDE 2 ). All studies reported important differences in the baseline characteristics of patients who had SDE versus SEEG, limiting any meaningful conclusions on how the 2 modalities truly compare.…”
Section: Discussionmentioning
confidence: 99%
“…As with other significantly different neurosurgical procedures, randomized ccontrolled trials (RCTs) comparing the 2 methods are virtually impossible 6 : only a handful of surgical programs have the versatility needed to offer both procedures, 3 and patients often have strong preferences given the significantly different approaches. 7 Over the past 20 years, the number of iEEG investigations without a subsequent therapeutic resection has tripled in the USA and Europe. 8 Clinical practice has become preference sensitive, rather than evidence based.…”
mentioning
confidence: 99%
“…If the seizure onset zone was thought to arise from a deep lesion or if there were a reason to record bilaterally, the use of depth electrodes might be favored 3 , 6 . Risk profiles differ between both approaches, and this also plays a role in choosing which modality to use 7 12 . Finally, each method of intracranial monitoring may have advantages over others, yet the decision to use a certain modality over another at many US institutions may have more to do with preferred clinical practice at a given center 3 .…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that previous results regarding the superiority of sEEG over SDE/DE may be driven by the data from extratemporal cases. 22,27,37,38 To the best of our knowledge, our study is the first to investigate the efficiency of intracranial monitoring approaches in a focused and uniform manner, in terms of patient population (TLE) and surgical treatment (ATL).…”
Section: Discussionmentioning
confidence: 99%